PENGGUNAAN GOOGLE MEET DAN KENDALANYA DALAM PEMBELAJARAN DARING BAHASA JEPANG DI SMAN 1 CIBARUSAH - Deliyana Hasanah (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2021)
This research aims to find out the use of google meet in Japanese online learning at SMAN 1 Cibarusah and the obstacles that occur to teachers and students while using google meet in Japanese online learning. The background of this research is based on the results of interviews with teachers of SMAN 1 Cibarusah that there are obstacles that occur to teachers and students in using Google Meet as a new platform in teaching and learning activities. This type of research is descriptive qualitative. The research instruments are observation, questionnaires and interview. Based on the research results, it is known that the use of google meet in Japanese online learning can overcome the limitations of the distance between teachers and students so that Japanese teaching and learning activities can still be carried out properly. However, some students and teachers are constrained by signals while using google meet. Videos and sounds are often paused, causing in students having difficulty in concentrating and being able to understand the material explanation from the teacher. In addition, there are other obstacles, namely the difficulty of teachers monitoring students while learning and difficulties in conducting assessments. The number of students in one class reaches 121 people so that the teacher cannot control the students one by one. Likewise, students experience fatigue, eyesore, passiveness, find it difficult to understand the learning material, and feel that the learning environment is unconducive.